Evidence of a Gene-for-Gene Relationship in the Oryza sativa - Magnaporthe grisea Pathosystem - Silué, Drissa; Notteghem, Jean Loup; Tharreau, Didier (Phytopathology, 2025)
A cross was made between two field isolates of pathogenic to rice. Full-sib crosses between F ascospores, followed by backcrosses to the female fertile parent GUY11, produced perithecia fertile enough for tetrad isolation. Genetic analysis of the pathogen revealed that avirulence to the rice cultivar Pi-n°4 is controlled by one gene ( ) unlinked to the gene MAT1-1, which is responsible for mating type. Additionally, resistance of Pi-n°4 was found to be controlled by one gene. Thus, existence of a gene-for-gene relationship was shown for the pathosystem .